The Chalcogen (S, Se, and Te) Doping Effects on the Structural and Electronic Properties of Anatase (101) TiO2 Thin Surface Layers: DFT Study - Ihsan Erikat; Manal Alkhabbas; Bothina Hamad; Waed Alahmad (International Journal of Photoenergy)
Doping TiO2 with chalcogen (S, Se, and Te) decreases its band gap and enhances the photocatalytic activity. However, doping TiO2 could create mid-gap states that trap the electrons and reduce the photocatalytic activity. Therefore, more investigation is needed to extrapolate clear insights for technological development. Density functional theory (DFT) is used to investigate the effects of doping chalcogens (X) (X=S, Se, and Te) in the two layers (2L) and four layers (4L) anatase (101) TiO2 surfaces. The structural and electronic properties as well as the band gap are investigated for the doping of one or two chalcogens in the TiO2 surface. The hybridization between the p chalcogen and 3d Ti as well as the 2p O orbitals causes the narrowing of the band gap. The substitutional doping of chalcogen in the TiO2 surface introduces new states in the band gap region and predicts the enhancement of visible light photoactivity. Among all the substitutional doping chalcogens in TiO2, the Te/TiO2 band gap is significantly lower than in the Se- and S-doping systems. The effects of the chalcogen doping depend on the concentration of the chalcogen as well as the number of layers in TiO2 surfaces.